Zinc finger CCHC-type protein related with seed size in model legume species Medicago truncatula - Mariana Radkova; Miglena Revalska; Daniela Kertikova; Anelia Iantcheva (Biotechnology & Biotechnological Equipment, 2019)
Legumes are one of the world's leading sources of nutrition, providing sustainable agriculture. They require minimal amounts of soil improvers (fertilizers) due to the ability to absorb nitrogen through symbiotic interactions with nitrogen-fixing soil microorganisms. The trend for human population growth requires an adequate growth in crop production. This directly depends on the seed size and number as well as on the leaf biomass. In turn, seed size has been the subject of selection programmers for all crops. In this study, we explored the relation between the function of the gene coding Zinc finger CCHC-type protein and flower morphology and seed size in the model legume species Medicago truncatula. M. truncatula lines with modified level of Zinc finger CCHC transcript and transcriptional reporters were developed and analysed by real-time polymerase chain reaction and expression of the GUS (β-glucuronidase) and green fluorescent protein (GFP) reporter genes. A tissue-specific GFP signal was detected in the anthers from overexpessing M. truncatula lines. The M. truncatula lines with knockdown expression showed direct relation between low transcription level of Mt-Zn-CCHC gene and strongly reduced seed size accompanied with short stems length and internodes.